THE EFFICIENCY OF DRYING PISANG AWAK BANANAS WITH THE HYBRID METHOD AND THE BREAKEVEN POINT OF ENGINEERING ECONOMICS - Pongpattanasiri, Chaitamlong; Amdee , Noppadol; Tantiwattanodom, Channarong (Life Sciences and Environment Journal, 2023)
This research objectives were to find out the efficiency of making dried bananas with hybrid methods; solar drying and hot air drying and to compare the costs of using the traditional method and hybrid methods using breakeven analysis. Pisang awak bananas are used for drying with a hybrid method; drying in the solar dome and hot-air oven. Pisang awak banana was grown in Suan Phueng district, Ratchaburi, harvested in stage 2, and kept for proper ripeness at stage 6. The experiment used 10 clusters of Pisang awak bananas sliced vertically into 688 pieces. The drying process started in a solar drying dome for 18 and 36 hours at 42oC and went on drying with hot-air ovens at 35oC and 40oC for 18 and 2 hours, respectively. The indicators used to measure the efficiency and quality of dried bananas were the percentage of moisture, color index, firmness, and percentage of shrinkage, including breakeven analysis. The results revealed that the most appropriate way to dry Pisang awak bananas was in the solar dome at 42oC for 18 hours, and a hot-air oven at 35oC for 18 hours. Dried bananas were 19.54% of moisture and were under Thai Industrial Standards of dried banana products (less than 21%). The color index results were 42.65, 6.23, and 22.32 of L*, a, and b*, respectively that the color of dried banana was golden brown with soft texture; 412±86.14b g. of firmness. The percentage of shrinkage was relatively low because of drying with low temperatures. Moreover, the breakeven analysis showed the producer could gain a profit after selling 5,832 pieces or 584 jars of 10-piece dried bananas for 7 Baht a piece. The hybrid method helps reduce drying time by 78.57% from 168 hours of the traditional drying method.